Adaptation of Minahasan architectural local wisdom to thermal comfort in resorts on Bangka Island (ARTEKS : Jurnal Teknik Arsitektur, 2025)
Bangka Island has challenges in tropical climate development such as limitations in the selection of efficient materials and energy, thus requiring a building concept that is adaptive to the climate. The Coral Eye Resort on Bangka Island is a building with a modern concept that adapts the local wisdom of Minahasa architecture to its building. The adaptation of traditional architecture to modern buildings is adaptive to the tropical climate because it can affect the thermal comfort of the building. This study aims to evaluate how the principles of local wisdom of Minahasa traditional architecture affect thermal comfort passively. This study uses a qualitative method with a case study approach to examine design elements such as building orientation and shape, local materials, openings, and spatial layout through observation techniques. Thermal comfort is tested through user perceptions collected through in-depth interviews, replacing the quantitative approach generally used in research related to thermal comfort. The results of the study indicate that the application of the principles of local wisdom of Minahasa traditional architecture, such as high roofs, large openings, and the use of local materials has an impact on increasing thermal comfort felt by users. The findings of this study provide insight into the implications of the theory of adaptation of Minahasa Traditional Architecture to thermal comfort in the context of modern buildings in coastal areas.
Keywords: Coral eye; Local wisdom; Thermal comfort; Traditional Minahasa architecture; Tropical climate